Monitoring Seasonal Shear Wave Velocity Changes in the Top 6 m at Garner Valley in Southern California With Borehole Data. Issue 23 (12th December 2022) - Qin, Lei; Steidl, Jamison H.; Qiu, Hongrui; Nakata, Nori; Ben‐Zion, Yehuda
Abstract: Subsurface structures play important roles in seismic ground motion, crustal hydrology, stability of the built environment, and more. Constraining temporal changes of subsurface shear wave velocity ( V S ) can provide useful information to all these topics and the growing field of hydrological monitoring with seismic velocity. Using borehole records at Garner Valley, CA, we estimate seasonal subsurface V S variations from impulse response functions (IRFs) of earthquake data (2005–2018) along with IRFs and cross‐correlation of cross‐hole experiment data (2015–2018). The inferred V S variations are up to ∼25% in the top 6 m and ∼10% at 2–5 m in depth. The V S variations correlate strongly with the water table depth changes, suggesting that the changes are mostly due to fluctuations of pore pressure in the shallow material. The shallow velocity changes alter the near‐surface conditions, can affect seismic hazard estimation, and may be improperly attributed to deeper processes without careful analysis. Plain Language Summary: Seismic properties of subsurface materials are of great importance for multiple topics including surface science, estimates of seismic ground motion, and performance of considerable infrastructure. Monitoring temporal changes of seismic velocities in the top few meters provides key information for structural design and better hazard estimates. The Garner Valley Downhole Array (GVDA) is a well‐instrumented test‐site facility that includes seismic and pore pressure sensors installed at different depth ranges. In this study, we use seismic recordings from the GVDA to infer variations in near‐surface shear wave velocity ( V S ) with high spatial resolution. The results reveal significant (∼25%) seasonal variations of V S in the top 6 m that correlate well with changes in the water table. This implies that the weak near‐surface soil is highly susceptible to variations in the fluid content and other loadings such as strong shaking generated by earthquakes. While the V S variations are concentrated in the top few meters, such changes may be improperly attributed to variations of deeper structures without high‐resolution data and methods. Key Points: We use earthquake and cross‐hole experiment data at Garner Valley, CA, to monitor shear wave velocity variations in shallow materials The seasonal variation of shear wave velocity is up to ∼25% in the top 6 m, mainly caused by pore pressure changes The changes of shallow seismic properties are relevant to ground motion hazard and environmental seismology